Domestic Violence And Its Impact Upon Everyday Life of Married Women- A Study From Durgapur, West Bengal - Indrani Ghatak (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2016)
Domestic violence is a global phenomenon and it is not restricted to any geographical area. It is very much prevalent in every society and hence it adversely affects a considerable section of women who are subjugated and deprived of status and respect due to this domestic violence. Women in all cultures, religions, classes and ethnic groups suffer from violence perpetrated against them in marital home. The pre-existing patriarchal ideological structure imposes a strong restriction on the movement of married women by constructing rigid gendered roles. The present paper will highlight certain findings based on interview conducted by the researcher upon some Bengali married women of Durgapur, the most popular industrial city of Burdwan district, West Bengal. The paper will discuss the married women`s individual perception about Domestic violence and how it affects everyday life of a woman.